The Effect of Temperature on Soot Properties in Premixed Ethylene Flames. Issue 9 (2nd September 2019) - Apicella, B.; Tregrossi, A.; Ciajolo, A.; Abrahamson, J.; Vander Wal, R.L.; Russo, C.
ABSTRACT: Soot nanostructure was analyzed in fuel-rich premixed laminar C2 H4 /O2 flames at a constant equivalence ratio of 2.4 and different maximum temperatures, namely, 1620 and 1690 K, obtained using different cold gas velocities. Flame structure and bulk properties of soot as H/C ratio, reactivity and absorption coefficient were investigated, along with morphological, nanostructural, and chemical features (using TEM, HRTEM, EELS). It was found that dehydrogenation and aromatization of soot occurring along the flames are favored at the beginning of the flame in higher flame temperature conditions. Nevertheless, it was noticeable that soot reaches rather similar final nanostructure and bulk properties, independently on the temperature, at least in the 1620–1690 K range investigated.